Existence of Multiple Solutions for Fourth-Order Elliptic Problem - Hua Gu; Tianqing An (Abstract and Applied Analysis)
By using the variant fountain theorem, we study the existence of multiple solutions for a class of superquadratic fourth-order elliptic problem with Navier boundary value condition.